PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN PAI KELAS V DI SEKOLAH DASAR NEGERI 4 RARANG - Giri Rahmat Hidayat (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
This study aims to determine the use of the jigsaw method in improving the learning outcomes of Islamic religious education for Grade V students at SD Negeri 4 Rarang. The type of research used in this research is Classroom Action Research (CAR), the data collection techniques used are tests, observation sheets, and documentation. From the results of this study it can be concluded that the learning process of Islamic religious education using the application of the jigsaw method can improve student learning outcomes, by fulfilling the KKM. Improved student learning outcomes can be seen from each cycle, in the pre-cycle the average classical learning mastery score of students was 63.16 (11 students) with a percentage of 36.66%, in the first cycle the average classical learning mastery value of students was 66 (15 students ) with a percentage of 50% and in cycle II the average number of students' classical learning completeness scores was 85.66 (25 students) with a percentage of 83.33%. In the learning process the researchers used the demonstration learning method by involving students directly in the learning process, as evidenced by using the jigsaw method it had increased the achievement of Grade V students at SD Negeri 4 Rarang. As a result students are able to accept the material conveyed and achieve a desired goal. This is a change in learning outcomes, especially subjects of Islamic religious education.